FUNCTIONING OF THE ONEIRIC ELEMENTS IN THE PSYCHO-BIOGRAPHICAL TRILOGY BY STEPAN PROTSIUK - Strilchyk B. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the psycho-biographical trilogy by Stepan Protsiuk (The Rose of the Ritual Pain, The Masks Fall Off Slowly and Black Apple) as the object of ideological and psycho-analytical discourses. Here the main peculiarities of Protsiuk’s prose manner have been established, the appropriateness of analyzing his trilogy from the oneiric point of view has been proved and the terms ‘the oneiric’, ‘oneirotext’ and ‘oneiric metaphor’ have been explained.